FILM DOKUMENTER GAYA EXPOSITORY “KAPTEN MUDITA” - R. Ayu Ardhia Pramesti; I Ketut Buda; I Gusti Ngurah Wirawan (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The documentary film "Kapten Mudita" is an audio visual media that tells the heroic story of Captain Mudita. Captain Mudita is one of the heroes of the Indonesian Independence fighters in Bali who came from Puri Kilian-Puri Agung Bangli in Bangli Regency. The discussion on the concept of the documentary film "Kapten Mudita" is formulated in one problem formulation, namely the visualization of the patriotism concept in the documentary film "Kapten Mudita" in an expository style. The method that used in this research is qualitative research methods. Data collection methods that related to the problems are carried out using the three methods, namely observation, interviews, and documentation. The data analysis was sharpened by the theory of expository and patriotism which was used as a knife of analysis and a handle in answering these problems. The research results from the visualization of the concept of patriotism in the documentary film "Kapten Mudita" in an expository style which is dissected with the three research methods, accompanied by expository theory and patriotism, the results that the documentary film "Kapten Mudita" is told with a three-act structure, namely the initial stage, the middle stage, and the final stage, the initial stage tells about the background of Captain Mudita, then the middle stage tells the about difficulties faced by Captain Mudita, then the final stage tells about the seconds of Captain Mudita's death, which is packed in an expository style with the concept of visual patriotism.